Trust in Contemporary Society - Sasaki, Masamichi (International Comparative Social Studies, 2019)
Trust in Contemporary Society, by well-known trust researchers, deals with conceptual, theoretical and social interaction analyses, historical data on societies, national surveys or cross-national comparative studies, and methodological issues related to trust. The authors illuminate contemporary issues of trust and distrust. Readership: All interested in trust research in psychology, sociology, political science, economics, organizational and management studies, history, comparative study, area studies, survey research.